Valuing Commercial Mortgages: An Empirical Investigation of the Contingent‐Claims Approach to Pricing Risky Debt - TITMAN, SHERIDAN; TOROUS, WALTER (Journal of Finance, 1989)
ABSTRACT This paper empirically investigates a contingent‐claims model of commercial mortgage pricing. We find that the magnitude of the observed default premia for a sample of nonprepayable fixed rate bullet mortgages can be explained by the contingent‐claims model. In addition, the model explains a significant proportion of the period‐to‐period changes in the default premia. However, given an assumed negative correlation between building value changes and interest rate changes, the model's risk structure tends to increase less steeply with increasing maturity than the observed risk structure.